UV-Curable Urethane Acrylate Resin from Palm Fatty Acid Distillate - Teo, Kim Teck; Hassan, Aziz Amir; Gan, Seng Neon (MDPI, 2018)
Palm fatty acid distillate (PFAD), is a by-product of the crude palm oil refining process. It comprises mainly of free fatty acids-around 45% palmitic and 33% oleic acids-as the major components. Ultra-violet (UV) curable urethane acrylate (UA) oligomers could be synthesized from PFAD, by the following procedure. A hydroxyl terminated macromer was first prepared by reacting PFAD with a mixture of isophthalic acid, phthalic anhydride, neopentagylcol (NPG), and pentaerythritol. The macromer was then reacted with 2-hydroxylethylacrylate (2HEA) and toluene diisocynate (TDI) to generate a resin, containing acrylate side chains for UV curable application. A series of UA resins were prepared by using 15, 25, 45, 55, and 70% of PFAD, respectively. The UA resin has M w in the range of 3,200 to 27,000. They could be cured by UV irradiation at an intensity of 225 mW/cm 2 . Glass transition temperature (T g ) of the cured film was measured by differential scanning calorimeter (DSC), and hardness of the film was determined by a pendulum hardness tester, according to American Society for Testing and Materials (ASTM)4366. The resins were used in a wood-coating application. All of the cured films showed good adhesion, hardness, and chemical resistance except for the one using the 70% PFAD, which did not cure properly.